Obesity, obstetric complications and cesarean delivery rate–a population-based screening study - Weiss, Joshua L; Malone, Fergal D; Emig, Danielle; Ball, Robert H; Nyberg, David A; Comstock, Christine H; Saade, George; Eddleman, Keith; Carter, Suzanne M; Craigo, Sabrina D; Carr, Stephen R; D'Alton, Mary E (American journal of obstetrics and gynecology, 2004)
This study was undertaken to determine whether obesity is associated with obstetric complications and cesarean delivery. A large prospective multicenter database was studied. Subjects were divided into 3 groups: body mass index (BMI) less than 30 (control), 30 to 34.9 (obese), and 35 or greater (morbidly obese). Groups were compared by using univariate and multivariable logistic regression analyses. The study included 16,102 patients: 3,752 control, 1,473 obese, and 877 morbidly obese patients. Obesity and morbid obesity had a statistically significant association with gestational hypertension (odds ratios [ORs] 2.5 and 3.2), preeclampsia (ORs 1.6 and 3.3), gestational diabetes (ORs 2.6 and 4.0), and fetal birth weight greater than 4000 g (ORs 1.7 and 1.9) and greater than 4500 g (ORs 2.0 and 2.4). For nulliparous patients, the cesarean delivery rate was 20.7% for the control group, 33.8% for obese, and 47.4% for morbidly obese patients. Obesity is an independent risk factor for adverse obstetric outcome and is significantly associated with an increased cesarean delivery rate.